Asymmetric, nano‐textured surfaces influence neuron viability and polarity. Issue 6 (5th March 2018) - Belu, Andreea; Yilmaz, Mehmet; Neumann, Elmar; Offenhäusser, Andreas; Demirel, Gokhan; Mayer, Dirk
Abstract: Three dimensional, nanostructured surfaces have attracted considerable attention in biomedical research since they have proven to represent a powerful platform to influence cell fate. In particular, nanorods and nanopillars possess great potential for the control of cell adhesion and differentiation, gene and biomolecule delivery, optical and electrical stimulation and recording, as well as cell patterning. Here, we investigate the influence of asymmetric poly(dichloro‐p‐xylene) (PPX) columnar films on the adhesion and maturation of cortical neurons. We show that nanostructured films with dense, inclined polymer columns can support viable primary neuronal culture. The cell‐nanostructure interface is characterized showing a minimal cell penetration but strong adhesion on the surface. Moreover, we quantify the influence of the nano‐textured surface on the neural development (soma size, neuritogenesis, and polarity) in comparison to a planar PPX sample. We demonstrate that the nanostructures facilitates an enhancement in neurite branching as well as elongation of axons and growth cones. Furthermore, we show for the first time that the asymmetric orientation of polymeric nanocolumns strongly influences the initiation direction of the axon formation. These results evidence that 3D nano‐topographies can significantly change neural development and can be used to engineer axon elongation. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1634–1645, 2018.